Efficacy and safety of camrelizumab for the treatment of cervical cancer: a systematic review and meta-analysis - Mi, Xiaodong; Tuo, Fei; Lin, Tong (Frontiers in Oncology, 2024)
BackgroundCervical cancer (CC) is a prevalent malignancy in women and ranks fourth in global cancer-related mortality. The prognosis for women with metastatic or recurring cervical cancer is unfavorable. Camrelizumab is a humanized high-affinity IgG4-kappa monoclonal antibody targeting programmed cell death 1 (PD-1), which has been progressively documented as a therapy for advanced cervical cancer with good result metrics. Nonetheless, a comprehensive investigation of Camrelizumab’s efficacy in treating cervical cancer has yet to be conducted.MethodsWe conducted a search across PubMed, Ovid Medline, Embase, Web of Science, Cochrane Library, Scopus, ProQuest, CNKI, Wan Fang, VIP database, and CBMdisc, restricting the establishment date of the databases to October 2024. The ROBINS-I Scale was utilized to evaluate the methodological quality of the included studies. Furthermore, information about CR, PR, SD, PD, ORR, DCR, median OS, median PFS, adverse events (AEs), and other relevant data was obtained. A meta-analysis was performed utilizing a random-effects model and effect size for illness.ResultsThis meta-analysis included six trials, including 238 people with CC. The aggregated outcomes for patients were as follows: CR (0.097, 95% CI: 0.032-0.186), PR (0.465, 95% CI: 0.291-0.638), SD (0.264, 95% CI: 0.124-0.403), PD (0.174, 95% CI: 0.051-0.296), ORR (0.577, 95% CI: 0.354-0.799), DCR (0.784, 95% CI: 0.652-0.916), AEs (all grades: 0.836, 95% CI: 0.629-1.000, ≥grade III: 0.472, 95% CI: 0.111-0.834). The predominant treatment-related adverse events included anemia (≤grade II: 0.295, 95% CI: 0.187-0.402; ≥grade III: 0.124, 95% CI: 0.018-0.230), elevated aspartate aminotransferase (≤grade II: 0.196, 95% CI: 0.013-0.380; ≥grade III: 0.030, 95% CI: 0.007-0.053), neutropenia (≤grade II: 0.206, 95% CI: 0.150-0.261; ≥grade III: 0.114, 95% CI: 0.066-0.162), thrombocytopenia (≤grade II: 0.295, 95% CI: 0.187-0.402), and fatigue (≤grade II: 0.174, 95% CI: 0.046-0.303).ConclusionsThis meta-analysis demonstrates that camrelizumab is efficacious and well-tolerated in patients with cervical cancer.Systematic review registrationhttps://www.crd.york.ac.uk/prospero/, identifier CRD42024527065.